2006
DOI: 10.1002/adem.200500248
|View full text |Cite
|
Sign up to set email alerts
|

The Experimental and Theoretical Study of Phase Equilibria in the Pd–Zn (‐Sn) System

Abstract: The binary Pd‐Zn system was assessed in the scope of this paper. The experimental data from the literature were used for the assessment, together with our own data obtained by SEM‐EDS analysis and by the DTA. The paper is focused particularly on the Pd‐Zn system, but the Pd‐Sn and Sn‐Zn systems are also analysed in this paper. Finally, first prediction of the isothermal sections of the ternary Pd‐Sn‐Zn system was made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…Further increasing the Pd:Zn ratios to 1:2, the intensity of PdZn peak at 336.1 eV is enhanced and becomes dominant at Pd:Zn 1:5. Although the XRD analysis confirmed the presence of the -PdZn alloy in PdZn deposited on TiO2 catalysts, the alloy is formed when the Zn mole fraction is within the range of 0.4-0.6 31 . These results suggest that increasing the ratio of Pd:Zn in the preparation increases the amount of Zn that is incorporated into the Pd lattice and so may simultaneously enhance the amount of PdZn alloy on the surface.…”
Section: Xps and Xaesmentioning
confidence: 87%
See 1 more Smart Citation
“…Further increasing the Pd:Zn ratios to 1:2, the intensity of PdZn peak at 336.1 eV is enhanced and becomes dominant at Pd:Zn 1:5. Although the XRD analysis confirmed the presence of the -PdZn alloy in PdZn deposited on TiO2 catalysts, the alloy is formed when the Zn mole fraction is within the range of 0.4-0.6 31 . These results suggest that increasing the ratio of Pd:Zn in the preparation increases the amount of Zn that is incorporated into the Pd lattice and so may simultaneously enhance the amount of PdZn alloy on the surface.…”
Section: Xps and Xaesmentioning
confidence: 87%
“…The Pd catalyst appears to transform into a PdZn alloy under a reductive atmosphere. The PdZn alloy can exist in different compositions with a broader stability region 31 , with unique alteration of Pd electronic charges. Rehybridisation of Pd(4d) -Pd(5s,5p) and a charge transfer between Pd(4d)  (Zn(4p) during the formation of Pd-Zn bonds increase the binding energy of the core and valence levels of Pd 30,44 .…”
Section: Catalystmentioning
confidence: 99%
“…9b). According to the Pd-Sn phase diagram [13], the PdSn 4 intermetallic is the only phase in equilibrium with the ␤-Sn when the Pd concentration in a Sn-Pd alloy is less than 20%. It is, therefore, presumed that these tiny grains represent the PdSn 4 phase, which form in the solidification stage due to the solubility limit.…”
Section: High Pd-concentration Case (X ≥ 05)mentioning
confidence: 99%
“…This reaction refers to a solid-solid reaction between Ni and Sn-Pd, which is a two-phase alloy consisting of ␤-Sn and PdSn 4 [13]. It was found that the PdSn 4 gradually migrates from the Sn matrix to the Sn-Pd/Ni interface during the solid-state reaction, enhancing the overall thickness (ı) of the reaction products.…”
Section: Introductionmentioning
confidence: 98%
“…7(a). The other part of the SneZnePd isothermal section (higher than 20 at.%) were determined based on the 400 C isothermal sections investigated by Vizdal et al [23] and the three constituent binary systems [22,24,25]. Fig.…”
Section: Sneznepd Isothermal Section At 260 Cmentioning
confidence: 99%